Survival Impact of Adjuvant Chemoradiotherapy in Resected Pancreatic Cancer - Eyyüp ÇAVDAR; Kubilay KARABOYUN; Yakup İRİAĞAÇ; Abdullah SAKİN; Yüksel BEYAZ; Okan AVCI (Namık Kemal Tıp Dergisi, 2025)
Aim: Pancreatic cancer (PC) is one of the most aggressive cancers, with a 5-year survival rate of less than 50% in resectable stages. The aim of this study was to determine the survival effect of adjuvant chemoradiotherapy (CRT) in resected PC. Materials and Methods: We retrospectively analyzed 156 patients with resected PC, who received adjuvant chemotherapy with/without CRT. The Cox regression and Kaplan-Meier analyses were used to determine the factors related to survival rate. Subgroup analyses were performed according to clinical characteristics. Results: The number of patients with lymph node metastases was statistically significantly higher in patients receiving CRT (p=0.007). No effect of CRT on both disease-free survival (DFS) and overall survival was detected (p>0.05). Subgroup analysis of DFS showed that adjuvant CRT was associated with poor prognosis in patients with in patients with in patients with low Eastern Collaborative Oncology Group performance scores (p=0.043), low T-stage (p=0.024), or low De-Ritis ratio (p=0.030). Subgroup analysis indicated that the overall survival benefit of adjuvant CRT was more significant in patients without diabetes mellitus (p=0.040), low serum carbohydrate antigen 19-9 levels (p=0.047), or low hemoglobin values (p=0.046). Conclusion: Our study has shown that the survival benefits of adding CRT to adjuvant chemotherapy in operated PC patients are limited. Patients who will receive CRT must be carefully selected according to their clinicopathological characteristics.